PRODUKTIVITAS JAMUR Auricularia spp. PADA KOMPOS SERBUK GERGAJI KAYU Falcataria mollucana - Sihati Suprapti; Djarwanto (Jurnal Penelitian Hasil Hutan, 2013)
Ear mushroom is one of edible wood rotting fungi that has been already consumed by community. Mushroom's media was made of sengon (Falcataria mollucana (1) Nielsen) sawdust with addition of 12 or 16% rice bran, 3.2% lime, 0.4% gypsum, urea or trisodiumphosphate 0.4% and water, then being composted for 1, 3, 5 and 7 days. Media samples were grouped into A and B, where sterilized media A were inoculated with brown ear mushrooms (Auricularia auriculae-judae HHBI-312, HHBI-326) and black ear mushrooms (Auricularia polytricha HHBI-318, HHBI-331), and those of media B were inoculated by black ear mushrooms (Auricularia polytricha HHBI-331). Biological Conversion Efficiency (BE) was calculated based on the ratio of the mushroom yield in fresh condition to the dry weight. Results indicated that the high yield of ear mushroom was obtained on composting media for 3 and 5 days periods. The average yield of Auricularia auriculae-judae HHBI-312, HHBI-326 on media A were 58.88 grams dan 60.51 grams (EB 10.96% and 10.92%), and for Auricularia polytricha HHBI-318, HHBI-331) were 67.5 grams and 101 grams (EB 12.38% dan 18.56%), respectively. Urea addition on the media tend to increase the BE value of A auricula-judae. Houvrer, it found that the yield and BE value of A. polytricha on media consist of urea were higher than that on media consist of trisodiumphosphate. The productivity of A. polytricha HHBI-331 on B-media added with 16% ricebran (102.06 g. BE 18.73%) revealed bigber than that which added with 12% ricebran (79.94 g. BE 17.59%). Therefore, A. auricula-judae HHBI-312 and A. polytricha HHBI-331 selected for further mushroom production.